Answer:
f(x) = 1/2(4 - x)(x - 1)(x - 2)
Step-by-step explanation:
Considering zero's and a coefficient, the function is:
f(x) = a(x - 4)(x - 1)(x - 2)
Considering y-intercept:
f(0) = a(0 - 4)(0 - 1)(0 - 2)
4 = a(-4)(-1)(-2)
4 = -8a
a = -1/2
So the function is:
f(x) = -1/2(x - 4)(x - 1)(x - 2) = 1/2(4 - x)(x - 1)(x - 2)
B. You can get this by factoring the bottom of the first expression and then cancelling the terms. Then multiply by the inverse of the second.

(a) For dx/dt=6, dy/dt = 2·6 = 12
(b) For dy/dt=2, 2 = 2·dx/dt ⇒ dx/dt = 1
_____
The value of x is irrelevant for this question.
=====
If your function is 2^x +1 or 2^(x +1), it needs to be written as such. The answer above applies to the function given.
Answer:
4z - 15
4(3) - 15
12 - 15
= -3
High school math? really?
Answer:
No
Step-by-step explanation:
The sample size wasn't big enough. It could only be a trend in that grade.